Curriculum policies and teacher training: Between reformist perspectives and possibilities in a democratic context (Research, Society and Development, 2024)
The work sought to analyze the proposals for educational reforms based on the Common National Curriculum Base (BNCC), their developments, changes in the curriculum and teacher training in the neoliberal context. Thus, we are anchored in the studies of Ball, Apple, Arroyo, Aguiar and Dourado, to understand the reformist kinesis in education and its relationship with the imperatives of economic policies, which disregards the culture and diversity of public schools, the real needs and conditions of educational establishments. Methodologically, the research presents a qualitative approach. Objectively it is exploratory, and documentary in terms of sources, as we intend to understand the phenomenon from now on in the sociopolitical context. Therefore, we point out the devaluation of the experiences of professionals who worked at the school, understanding the BNCC as a homogeneous, prescriptive and (re)producing document of inequalities. Thus, it was observed that there is a discrepancy between what the document requires and the reality of Brazilian public schools. However, following the change in the political context, there was an opening for dialogue and discussion about the need to revoke the BNC-Formação.